Challenges and Opportunities of Cultural Tourism Development: Bangladesh Perspective - Hossain, Md Afjal; Nowreen, Samshad (Dhaka University Journal of Business Studies, 2023)
Many tourists have changed their tastes and they now avoid mass visited attractions and destinations. They now like to travel to natural attractions and destinations. Human beings are one of the natural attractions. Tourists basically want to know the unknown people and their customs and traditions, explore different cultures of different areas or nations, and experience those firsthand. They want to experience other people’s lives and behaviour, and enjoy their ways of interaction with others. Thus both tourists and local people come to know each other’s cultures. Cultural tourism has occupied an important position among many tourists and in the tourism system of many destination countries. Many destination countries are successfully presenting their cultures to attract cultural tourists to their destinations to observe their cultures. Bangladesh, geographically and historically, takes the pride of its rich, unique and lively culture. Development of cultural tourism in Bangladesh will add a new dimension to our existing tourism system. This will ultimately help attract more visitors in Bangladesh and spread a better image of the country’s tourism in the global tourist market. As such, to develop tourism, particularly cultural tourism, Bangladesh should pay due emphasis to present the cultural factors in its tourism activities and attract more tourists in the country. Journal of Business Studies, Vol. XLII, No. 2, August 2021 Page 97-112